Providing localized data on greenhouse gas emissions from livestock systems - Merbold, Lutz (International Livestock Research Institute, 2020)
Lutz Merbold, head of Mazingira Centre at ILRI and co-principal investigator in the Programme for Climate-Smart Livestock (PCSL) explains how the program will collect localized data on greenhouse gas emissions from livestock systems in eastern Africa. The PCSL is financed and coordinated by the German Corporation for International Cooperation GmbH (GIZ), commissioned by the Government of the Federal Republic of Germany. Read more about the PCSL project here: https://www.ilri.org/news/program-sup...